Food systems transformation in Vietnam – research and collaboration lay the foundation - Huynh, Tuyen; Pham, Huong; Lundy, Mark M. (DLG-Verlag GmbH, 2023)
Vietnam aims to transform its food systems in a transparent, responsible and sustainable manner. To help achieve this, the new CGIAR research initiative “Sustainable Healthy Diets through Food Systems Transformation” (SHiFT) is working with the emerging multi-stakeholder platforms in the country in order to support the planning and implementation of specific activities. This article demonstrates success already achieved.